3(2x+4)=-4(x-2)

Simple and best practice solution for 3(2x+4)=-4(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+4)=-4(x-2) equation:



3(2x+4)=-4(x-2)
We move all terms to the left:
3(2x+4)-(-4(x-2))=0
We multiply parentheses
6x-(-4(x-2))+12=0
We calculate terms in parentheses: -(-4(x-2)), so:
-4(x-2)
We multiply parentheses
-4x+8
Back to the equation:
-(-4x+8)
We get rid of parentheses
6x+4x-8+12=0
We add all the numbers together, and all the variables
10x+4=0
We move all terms containing x to the left, all other terms to the right
10x=-4
x=-4/10
x=-2/5

See similar equations:

| 5(b-3)=5b-9 | | 2(x+1)+(3x+1)=4(x+2) | | -2k+20=3k | | -16n-23.3=16.99n-56.29 | | 4/5y-3/2=-8/3 | | -16n-23.3=16.99n-5629 | | 2x+6+9=21 | | 112+90+73+x=360 | | X+x-12=56 | | 3.5(r+1)=2r+3.5 | | 1/8m=5/8 | | 4(8-c)=8c+16+6 | | 2−3a=8−2(2a+5) | | -2x+8=3x+12 | | 1.36(n-6)=-3.8n-3.0 | | 4c+7=-(c-4) | | 6+c/2=8 | | y/9-3=-12 | | 4x=21-18 | | -11-3n=16 | | F(8)=5n+8 | | 6(2a-6)=-2-5a | | 42n-3=17n+12 | | 2/3y-3=3/4 | | 0.55(100n+8)=0.6(85n+14) | | 3(3-5x)-5(7x-8)=4x-4-1 | | -2x+23=3(x-4) | | 2x-1-6=-2 | | d/3+4=12 | | -13=5/2(2+8x)-2 | | 4x2+32x+7=0 | | -91=g/7-101 |

Equations solver categories